2017
DOI: 10.1002/pssb.201600784
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Design Equation for the Maximum Deflection in a Class of Auxetic Sectorial Plates

Abstract: Auxetic materials are solids that exhibit negative Poisson's ratio. The effect of material auxeticity (i.e., negativity of Poisson's ratio) is investigated herein on the maximum deflection of sectorial plates with Simply‐Supported straight edges and Free curve edge (SSF). To aid the designer, an accurate and conveniently executable semi‐empirical model has been developed herein, which is valid for the entire range of Poisson's ratio of isotropic solids and for the plate's sectorial angle from 30 to 90 degrees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The extent of anisotropy increases when the array goes to the extremes, thereby leading to extreme negative Poisson’s ratios. The results from this paper, in conjunction with earlier works on auxetic beams [40,41], auxetic rods [42,43,44], auxetic plates [45,46,47,48,49,50,51,52], auxetic shells [53,54], auxetic composites [55,56,57,58,59,60,61,62] and 2D metamaterial structures [63,64], would avail more design options for the engineer in developing novel load bearing materials and structures.…”
Section: Discussionsupporting
confidence: 71%
“…The extent of anisotropy increases when the array goes to the extremes, thereby leading to extreme negative Poisson’s ratios. The results from this paper, in conjunction with earlier works on auxetic beams [40,41], auxetic rods [42,43,44], auxetic plates [45,46,47,48,49,50,51,52], auxetic shells [53,54], auxetic composites [55,56,57,58,59,60,61,62] and 2D metamaterial structures [63,64], would avail more design options for the engineer in developing novel load bearing materials and structures.…”
Section: Discussionsupporting
confidence: 71%
“…In his paper An accurate design equation for the maximum defl ection of SSF sectorial plates made from auxetic materials Lim [20] explores the interlink between auxeticity and mechanics of plates and solids. He examines the relation between Poisson's ratio of isotropic 3D material systems and maximum defl ection of sectorial plates with Simply-Supported straight edges and Free curve edge (SSF).…”
Section: In the Paper Microstructural Effects On The Poisson's Ratio mentioning
confidence: 99%
“…It has also been found that novel properties, distinct from conventional or auxetic materials, arise when a composite structure is made from both conventional and auxetic materials. In addition to a recent comprehensive survey of auxetic materials and structures [ 37 ], the reader is also referred to a recent focus issue on “auxetics and other systems of anomalous characteristics” [ 38 , 39 , 40 , 41 , 42 ], as well as papers in this special issue [ 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%